2023
DOI: 10.1093/rheumatology/kead013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of baricitinib on microglia and STAT3 in a region with a weak blood–brain barrier in a mouse model of rheumatoid arthritis

Abstract: Objectives In patients with rheumatoid arthritis (RA), baricitinib not only improves arthritis symptom severity, but also patients’ neuropsychological symptoms, such as depression and fatigue. However, the cellular mechanisms through which baricitinib can affect neural activity is unexplored. While the blood-brain barrier (BBB) permeability of this drug remains unclear, Janus kinase inhibitors (JAKi) might reach the area postrema (AP), which is a unique brain region with a weak BBB function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In general, most systemically administered chemical compounds can barely cross the blood–brain barrier (BBB). However, using a mouse RA model, Matsushita et al showed that baricitinib acts on a part of brain where the BBB is weak [ 39 ]. In our present data, baricitinib treatment, more than celecoxib treatment, altered the pattern of gene expression in the DRG of CAIA mice in a way similar to that seen in the control group, although both treatments did improve arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most systemically administered chemical compounds can barely cross the blood–brain barrier (BBB). However, using a mouse RA model, Matsushita et al showed that baricitinib acts on a part of brain where the BBB is weak [ 39 ]. In our present data, baricitinib treatment, more than celecoxib treatment, altered the pattern of gene expression in the DRG of CAIA mice in a way similar to that seen in the control group, although both treatments did improve arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis in cancer patients has identified sex-related differences in pharmacokinetics and, in particular, slower elimination of tyrosine kinase inhibitors in females ( Huang et al, 2022 ; Özdemir et al, 2022 ). Other inhibitors of tyrosine kinases that are also in clinical trial for the treatment of AD include dasatinib, a potent inhibitor of Abl and Src and the JAK inhibitor, baricitinib ( Matsushita et al, 2023 ), although sex-related differences in the pharmacokinetics of these have not been reported.…”
Section: Is There Evidence Of Sex-related Differences In Response To ...mentioning
confidence: 99%
“…Süß et al [ 12 ] revealed the activation of microglia (using integrin subunit α-M and ionized calcium-binding adapter molecule 1 as microglial maker) in the cortex, striatum, and thalamus in tumor necrosis factor-alpha (TNF-α) transgenic mice and showed that TNF inhibitors suppressed the activation of microglia. Recently, we reported that microglia are activated in the area postrema of CIA mice and that Janus kinase signal transducers and transcription inhibitor activators suppress their activation [ 15 , 16 ]. However, it remains unclear when inflammatory changes occur in the CNS and how they spread spatially in these mouse models.…”
Section: Introductionmentioning
confidence: 99%